Contribution of lipophilicity to the clinical effects of drugs - A. S. Skotnikov; M. V. Melnik; E. A. Zinina; I. V. Sivertseva (Российский кардиологический журнал)
The article is devoted to a detailed analysis of the action of various drugs used in the treatment of hypertension and atherogenic dyslipidemia, depending on their ability to dissolve in fatty media (lipophilicity). The authors analyze connection between the lipophilicity level of drugs and their pharmacokinetics, drug-drug interactions, the manifestations of clinical effects and organ protection, as well as their ability to influence the prognosis of comorbid patients. Using angiotensin-converting enzyme inhibitors, calcium channel blockers, and statins as examples, the authors explain the practical significance of pharmacological parameters such as plasma protein binding and distribution volume, and also develop an understanding of the importance of its routine use in order to obtain clinical benefits for patients.